A novel generalized stress invariant-based strength model for inter-layer failure of FFF 3D printing PLA material. (August 2020) - Yao, Tianyun; Zhang, Kai; Deng, Zichen; Ye, Juan
Abstract: As an inherent defect of Fused Filament Fabrication 3D printing materials, the occurrence of inter-layer failure reduces the tensile failure strength significantly. To better understand this defect and improve the mechanical properties of FFF 3D printing materials and structures, the distribution and basic mechanical principles of inter-layer failure are explored in detail in this study. Tensile experiments of a wide range of layer thicknesses (0.1 mm to 0.6 mm) and printing angles (0° to 90°) are carried out to find the distribution range and features of inter-layer failure. Additionally, a novel generalized strength model is established to predict the tensile failure strength of inter-layer failure of FFF 3D printing PLA material. Experimental results show that the distribution range of inter-layer failure increases significantly as the layer thickness increases from 0.1 mm to 0.6 mm, and inter-layer failure tends to occur when the printing angle and the tensile failure strength are small. All the Root Mean Square (RMS) error between theoretical results and experimental data of tensile failure strength of inter-layer failure are less than 10%. Therefore, the theoretical model established in this study has the ability to predict the tensile failure strength of inter-layer failure of FFF 3D printing PLA material accurately. Graphical abstract: Unlabelled Image Highlights: The distribution and regularities of inter-layer failure of FFF PLA material are explored experimentally. The principle of inter-layer failure is explained based on hypothesis of transversely isotropy and hypothesis of double-stress. A novel generalized strength criterion is established to predict the tensile failure strength of inter-layer failure of FFF PLA material. Generalized maximum tensile failure strength and slowly changing interval of tensile failure strength are discovered.